Bone tools from Beds II–IV, Olduvai Gorge, Tanzania, and implications for the origins and evolution of bone technology. Issue 148 (November 2020) - Pante, Michael; Torre, Ignacio de la; d'Errico, Francesco; Njau, Jackson; Blumenschine, Robert
Abstract: The advent of bone technology in Africa is often associated with behavioral modernity that began sometime in the Middle Stone Age. Yet, small numbers of bone tools are known from Early Pleistocene sites in East and South Africa, complicating our understanding of the evolutionary significance of osseous technologies. These early bone tools vary geographically, with those in South Africa indicating use in foraging activities such as termite extraction and those in East Africa intentionally shaped in a manner similar to lithic tool manufacture, leading some to infer multiple hominin species were responsible for bone technology in these regions, with Paranthropus robustus assumed to be the maker of South African bone tools and Homo erectus responsible for those in East Africa. Here, we present on an assemblage of 52 supposed bone tools primarily from Beds III and IV, Olduvai Gorge, Tanzania, that was excavated by Mary Leakey in the late 1960s and early 1970s, but was only partially published and was never studied in detail from a taphonomic perspective. The majority of the sites from which the tools were recovered were deposited when only H. erectus is known to have existed in the region, potentially allowing a direct link between this fossil hominin and bone technology. Our analysis confirms at least six bone tools in the assemblage, the majority of which are intentionally flaked large mammal bones. However, one of the tools is a preform of the oldest barbed bone point known to exist anywhere in the world and pushes back the initial appearance of this technology by 700 kyr. Highlights: This research expands on the small sample of bone tools known from the Early Stone Age site of Olduvai Gorge, Tanzania . The confirmed tools include the oldest preform of a barbed bone point that predates others by at least 700 kyr. Homo erectus was likely the primary maker and user of bone tools at Olduvai Gorge, Tanzania.